Kant og den moderne pliktbevissthet - Nerheim, Hjördis (Studier i Pædagogisk Filosofi, 2012)
Kant’s rejection of rebellion as a political right seems to be problematic for his concept of duty. The paper discusses the trial of the Holocaust perpetrator Adolf Eichmann as a possible case against Kant’s political philosophy. It argues, however, that Kant in his Critique of Judgment and in his philosophy of religion has articulated a very sophisticated point of view.